# Differentiate the function.

Rewrite this as:

`y=(lnx)^-1`

We can take the derivative by power rule and chain rule. Chain rule is the derivative of the inner function.

`y'= -(ln(x))^-2 * (1/x)`

This simplifies to:

`y'=-1/(x(lnx)^2)`

You need to differentiate the function with respect to x, using the quotient rule, such that:

`f'(x) = (1/(ln x))'`

`f'(x) = (1'*(ln x) - 1*(ln x)')/(ln^2 x)`

`f'(x) = (0*ln x - 1/x)/(ln^2 x)`

`f'(x) = -1/(x*ln^2 x)`

**Hence, evaluating the derivative of the given function, yields` f'(x) = -1/(x*ln^2 x).` **

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now